KEHIDUPAN SOSIAL ANAK DENGAN PENYANDANG CONDUCT DISORDER - Badriyah, Lailatul; Three Sartini, Nopa; Zubaidah, Zubaidah (GHAITSA : Islamic Education Journal, 2020)
This study aims to look at the social characteristics of children or adolescents with people with behavioral disorders. In DSM-IV Conduct Disorder is a pattern of behavior that is persistent and repetitive, shown by behavior that is not in accordance with the value of truth adopted by the community or does not comply with social norms for the average age. These symptoms are aggression against people or animals, damage to goods, like lying or stealing and breaking the rules. This research is a qualitative research study with a case study approach that takes a subject who is fifteen years old, where this research is based on the natural side of a case that produces data from respondents or observed behaviors and situations. This approach is in accordance with the beginning of this research, which is to look for facts from one of the children with behavioral disorders at school who are then interviewed and given a DCM instrument (check list of problems) and also observation or observation, directly. After that the data is then matched with previous theory and research. And the results state that behavior disorder is a pattern of behavior that violates social norms that are carried out repeatedly. The factors are family, biological and individual. In this study, one of the triggers for children with behavioral disorders is because the parent child lacks supervision and every child talks about his achievements, but his parents always assume that he is lying when the child is hoping for praise.